Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi: Kalimantan Selatan, Sulawesi Barat, Nusa Tenggara Barat, Bengkulu 2023-2024 - Muhammad Hizkil Ramadhan; Nova Dwi Ramadhan; Aditya Putra Pratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The diversity of the age of educators in Indonesia affects the quality of education in each region. The uneven age distribution, with a shortage of productive teachers and an increasing number of teachers approaching retirement, is a challenge in equalizing the quality of education. This study uses a quantitative approach with descriptive analysis to analyze the age distribution of educators in four provinces: South Kalimantan, West Sulawesi, West Nusa Tenggara, and Bengkulu. Data from KEMENDIKBUDRlSEK 2023 were analyzed using SPSS to calculate the mean and median, presented in tables, histograms, and frequency polygons. The results of the study show significant differences in the age distribution of educators and the imbalance in the number of teachers and students in several provinces, which have an impact on the quality of education. This study provides important insights for more effective education policies by considering the age distribution of educators.